A high-performance atmospheric radiation package: With applications to the radiative energy budgets of giant planets. (September 2018) - Li, Cheng; Le, Tianhao; Zhang, Xi; Yung, Yuk L.
Highlights: A new generic parallel radiative transfer model is developed for scattering atmospheres (HARP). Both line-by-line and correlate- k opacity models are implemented. HARP is applied to all giant planets in the solar system. The radiative cooling/heating structures of Saturn, Uranus and Neptune are analyzed for the first time. Abstract: A High-performance Atmospheric Radiation Package (HARP) is developed for studying multiple-scattering planetary atmospheres. HARP is an open-source program written in C + + that utilizes high-level data structure and parallel-computing algorithms. It is generic in three aspects. First, the construction of the model atmospheric profile is generic. The program can either take in an atmospheric profile or construct an adiabatic thermal and compositional profile, taking into account the clouds and latent heat release due to condensation. Second, the calculation of opacity is generic, based on line-by-line molecular transitions and tabulated continuum data, along with a table of correlated- k opacity provided as an option to speed up the calculation of energy fluxes. Third, the selection of the solver for the radiative transfer equation is generic. The solver is not hardwired in the program. Instead, based on the purpose, a variety of radiative transfer solvers can be chosen to couple with the atmosphere model and the opacity model. We use the program to investigate the radiative heating and cooling rates of all four giant planets in the Solar System. Our Jupiter's result is consistent with previous publications. Saturn has nearly perfect balance between the heating rate and cooling rate. Uranus has the least radiative fluxes because of the lack of CH4 and its photochemical products. Both Uranus and Neptune suffer from a severe energy deficit in their stratospheres. Possible ways to resolve this issue are discussed. Finally, we recalculate the radiative time constants of all four giant planet atmospheres and find that the traditional values from (Conrath BJ, Gierasch PJ, Leroy SS. Temperature and Circulation in the Stratosphere of the Outer Planets. Icar. 1990;83:255–81) are significantly overestimated.